Suicide Deaths in China: An Analysis of Forensic Cases - Dong Zhao; Longlong Wang; Kun Wang; Zhimin Wang; Eradil Orazhkan (Wolters Kluwer Medknow Publications, 2016)
Suicide cases are often encountered during death investigations in forensic medicine. In this study, through a comparative analysis of our own data of 98 suicide cases and previous reports from various forensic institutions in China, we analyzed the risk factors of Chinese suicides and explored the implications thereof from a forensic point of view. Moreover, the age and sex differences, means, causes, and other concerns regarding suicide are discussed along with a review of the literature.